2018
DOI: 10.1101/487579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Renal medullary carcinomas depend uponSMARCB1loss and are sensitive to proteasome inhibition

Abstract: 23 24 48 identify a synthetic lethal relationship that may serve as a therapeutic approach for patients with 49 SMARCB1 deficient cancers. 50 51 52

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…A single research reported the possibility that SMARCB1 might be involved in regulating UPS activity through modulating the transcription of UPS-related proteins [ 35 ]. Moreover, using computational modeling, the conserved imperfect repeat unit (Rpt1) domain of SMARCB1 was identified to share structural similarity with the PLAA family of the ubiquitin-binding (PFU) domain of phospholipase A2-activating protein (PLAA) which is required for the interaction with ubiquitin [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A single research reported the possibility that SMARCB1 might be involved in regulating UPS activity through modulating the transcription of UPS-related proteins [ 35 ]. Moreover, using computational modeling, the conserved imperfect repeat unit (Rpt1) domain of SMARCB1 was identified to share structural similarity with the PLAA family of the ubiquitin-binding (PFU) domain of phospholipase A2-activating protein (PLAA) which is required for the interaction with ubiquitin [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microscopically, RMC tumors are densely packed with eosinophilic‐cytoplasmic epithelial cells in cribriform orientation and cytoplasmic inclusions (Swartz et al, ). Interestingly, patients with RMC also harbor deletions in SMARCB1 , similar to RTK (Cheng et al, ; Fox et al, ; Hong et al, ; Msaouel, Tannir, & Walker, ; Table ). However, unlike RTK, which has very few other recurrent genetic events, RMC is also associated with t(2;10)(p23.2;q22.2) translocation that leads to anaplastic lymphoma kinase (ALK) and vinculin fusions (Mariño‐Enríquez et al, ).…”
Section: Renal Cell Tumors: Most Common Renal Malignancies In Adultsmentioning
confidence: 99%
“…Currently, there is a need for cell line models for RMC to provide a crucial tool for the investigation of novel therapies for patients affected with RMC. A recent study by Hong et al 20 managed to produce two primary tumor cell lines from two separate patients using a ROCK inhibitor (Y‐27632) based methodology 21 to produce a successful culture. Both cell lines and the tumors from which they were derived had the expected loss of SMARCB1 function and the cell lines demonstrated an in vitro response to bortezomib 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Hong et al 20 managed to produce two primary tumor cell lines from two separate patients using a ROCK inhibitor (Y‐27632) based methodology 21 to produce a successful culture. Both cell lines and the tumors from which they were derived had the expected loss of SMARCB1 function and the cell lines demonstrated an in vitro response to bortezomib 20 . Neither of the primary tumor lines developed in this study were capable of producing tumor xenografts and so this study relied on utilizing the SMARCB1‐deficient rhabdoid cell line G401 as a substitute for an actual RMC cell line in its in vivo studies 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation